Mineralogical and chemical characterization of mining waste and utilization for carbon sequestration through mineral carbonation - Molahid, Verma Loretta M.; Mohd Kusin, Faradiella; Syed Hasan, Sharifah Nur Munirah (Springer, 2023)
This study attempts to evaluate the potential of reusing mining waste as feedstock mate- rial for carbon dioxide sequestration through mineral carbonation. Characterization of mining waste was performed for limestone, gold and iron mine waste, which includes physical, mineralogical, chemical and morphological analyses that determine its potential for carbon sequestration. Mining activities have often been associated with the issues of waste generation, while mining is considered a carbon-intensive industry that contributes to the increasing carbon dioxide emission to the atmosphere. This study attempts to evaluate the potential of reusing mining waste as feedstock material for carbon dioxide sequestration through mineral carbonation. Characterization of mining waste was performed for limestone, gold and iron mine waste, which includes physical, mineralogical, chemical and morphological analyses that determine its potential for carbon sequestration. The samples were characterized as having alkaline pH (7.1–8.3) and contain fne particles, which are important to facilitate precipitation of divalent cations. High amount of cations (CaO, MgO and Fe2O3) was found in limestone and iron mine waste, i.e., total of 79.55 and 71.31, respectively, that are essential for carbonation process. Potential Ca/Mg/Fe silicates, oxides and carbonates have been identifed, which was confrmed by the microstructure analysis. The limestone waste composed majorly of CaO (75.83), which was mainly originated from calcite and akermanite minerals. The iron mine waste consisted of Fe2O3 (56.60), mainly from magnetite and hematite, and CaO (10.74) which was derived from anorthite, wollastonite and diopside. The gold mine waste was attributed to a lower cation content (total of 7.71), associated mainly with mineral illite and chlorite– serpentine. The average capacity for carbon sequestration was between 7.73 and79.55, which corresponds to 383.41 g, 94.85 g and 4.72 g CO2 that were potentially sequestered per kg of limestone, iron and gold mine waste, respectively. Therefore, it has been learned that the mine waste might be utilized as feedstock for mineral carbonation due to the availability of reactive silicate/oxide/carbonate minerals. Utilization of mine waste would be benefcial in light of waste restoration in most mining sites while tackling the issues of CO2 emission in mitigating the global climate change.